THE EFFECTIVENESS OF VIDEO BLOGGING IN TEACHING SPEAKING VIEWED FROM STUDENTS’ LEARNING MOTIVATION - Lisa Rakhmanina; Dian Kusumaningrum (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
The research is aimed at finding out: (1) the difference between videobloggingstrategy and expository strategy for teaching speaking; (2) the difference between students who have high and low motivation in speaking ability; and (3) the interaction between teaching strategies and motivation in teaching speaking. Related to the aims of the research, an experimental method is carried out in Faculty of Law, University Prof. Dr. Hazairin, SH, Bengkulu. The population was all of the second semester in 2016/2017 academic year. Two out of four classes consisting of 25 students from each were taken as the sample by applying cluster random sampling. They were Class A as the experimental group and Class B as the control group. The experimental group was learning speaking using Videoblogging strategy, while the control group was learning using expository strategy. The instruments for collecting the data were a questionnaire on speaking motivation and a speaking test. Cronbach Alpha formula was used to measure the reliability of items on the instruments. Based on the two formulas, it was found that all of 44 items in the speaking motivation questionnaire were valid. Furthermore, it was found out that the data were in normal distribution and homogeneous based on the normality testing and homogeneity testing. The writer analyzed the speaking test scores of students who had high and low reading motivation in the experimental and control groups. Multifactor Analysis of Variance (ANOVA) and Tuckey test were applied.Based on the result of data analysis, it can be concluded that: (1) Learning speaking through videoblogging is more effective than expository strategy ; (2) the students who have high learning motivation have higher speaking ability than those who have low one; and (3) there is an interaction between teaching strategies and motivation for the teaching of speaking.Therefore, it is recommended that: (1) teachers apply videoblogging process in teaching students speaking; (2) to promote students’ learning motivation, it is important to give students chance to develop their own ideas and share the ideas in their personal videoblog (vlog); and (3) future researchers may conduct the same kind of research with different sample and condition.